Peningkatan Literasi Digital dan Kemanusiaan Melalui Powerpoint sebagai Media Pembelajaran bagi Santri Pondok Pesantren Asshodiqiyah - Rasdi; Suran Ningsih, Ayup; Niravita, Aprila; Prabowo, Muchammad Shidqon; Wijayanto, Indung; Fiorentina, Prita; Komariyah, Maulida Nurul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
People's lack of understanding of digital media results in misuse which has consequences for personal and social life. Social media is present as part of internet development. Its presence offers easy and new ways of interacting, communicating, and socializing with the support of interesting features. The number of social media users in Indonesia is dominated by teenagers, so the impact is felt by teenagers. Good use can improve achievement, whereas bad use can have negative consequences for children and adolescents. We need to respond to technological developments that are bringing us to the Industrial Revolution 4.0 wisely. This is what makes Digital Literacy very necessary. Self-understanding of digital technology movements requires us to learn more deeply about material related to digital literacy. To be able to use the internet well, everyone, including students, must have good digital literacy. To be able to use the internet well, it is necessary to strengthen the literacy of students. Apart from that, there needs to be protection so that the internet is used only for good, and teachers must direct students to filter negative things from the internet. After learning about Digital Literacy and Humanity, Santri will be given training on how to prepare PowerPoint as a learning medium. Improving skills in preparing learning media based on digital literacy is an important thing for students to develop.